Peran Pendidik Dalam Menanamkan Nilai-Nilai Keteladanan Pada Anak Didik - Nur Hidayat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Factors within an exemplary educator absolutely necessary. The students will be good or not, moral or not, and character or not it can not be separated from the influence and role of personality and self exemplary educator who has the attitude, morale and good personality too. Thus began instilling the good qualities in themselves an educator first, and then to our students. It is therefore a good educator can follow the slogan that has been delivered by an expert of Education we are Ki Hajar Dewantara, with the following concept: that a good educator should have the principle of â€œIng ngarsa tuladha sungâ€ (lead by example), â€œing intermediate Mangun intention â€œ(fostering the spirit of selfbuild) andâ€ Handy Tutwuri â€œ(liberated while giving strength). In addition, an educator should also have properties, Rabbani, patient, sincere, and honest. Keywords : educators, exemplary, honesty, patience, and sincere.